Scaling Up Sweetpotato through Agriculture and Nutrition (SUSTAIN) in Rwanda - Sindi, K.; Ndirigue, J. (International Potato Center, 2015)
The SUSTAIN project aims to reach at least 60,000 direct smallholder beneficiaries and 250,000 indirect beneficiaries in four districts in Rwanda by 2018 with improved varieties and appropriate nutrition information and counseling for caregivers of infants and young children. This flyer outlines the progress made towards this objective between June 2014 to July 2015.